Determination of Climate and Social Community Factors in Coronavirus Disease-19 Spread Distribution - Faradiba, Faradiba; Zet, Lodewik (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Coronavirus Disease-2019 (COVID-19) is very shocking to the world. Until mid-2020, this virus has not yet found a vaccine that can be produced and can be applied en mass across the country. The spread of COVID-19 differs between regions which implie that regional characteristics have an influence on the rate of growth. Regional and social climate factors are thought to have a role in the growth rate of COVID-19. AIM: This study aims to find the role of climate and social society on the spread of COVID-19. METHODS: This research uses OLS regression analysis method, and then continued with Chi-squared Automatic Interaction Detector analysis to find the segmentation of the role of climate and social factors on the daily growth rate of COVID-19 in positive and deceased patients. RESULTS: The results of this study state that all independent variables of the study have a significant effect on the spread of COVID-19, with R-squared values in positive and deceased patients, respectively 61.1% and 70.0%. Strategic steps are needed to carry out policies that are targeted, effective and efficient. CONCLUSION: The results of this study can be a reference for the government in determining policies to reduce the growth rate of COVID-19, by focusing on areas that have poor sanitary environment and area are on Java Island.